Optical signatures of the coupled spin-mechanics of a levitated magnetic microparticle - Wachter, Vanessa; Bittencourt, Victor A. S. V.; Xie, Shangran; Sharma, Sanchar; Joly, Nicolas; Russell, Philip St. John; Marquardt, Florian; Viola Kusminskiy, Silvia (Journal of the Optical Society of America B-Optical Physics, 2021)
We propose a platform that combines the fields of cavity optomagnonics and levitated optomechanics to control and probe the coupled spin-mechanics of magnetic dielectric particles. We theoretically study the dynamics of a levitated Faraday-active dielectric microsphere serving as an optomagnonic cavity, placed in an external magnetic field and driven by an external laser. We find that the optically driven magnetization dynamics induces angular oscillations of the particle with low associated damping. Further, we show that the magnetization and angular motion dynamics can be probed via the power spectrum of the outgoing light. Namely, the characteristic frequencies attributed to the angular oscillations and the spin dynamics are imprinted in the light spectrum by two main resonance peaks. Additionally, we demonstrate that a ferromagnetic resonance setup with an oscillatory perpendicular magnetic field can enhance the resonance peak corresponding to the spin oscillations and induce fast rotations of the particle around its anisotropy axis. (C) 2021 Optical Society of America
Created from Fastlane, WoS look-up